High-risk stress fractures: evaluation and treatment - Boden, B. P.; Osbahr, D. C. (Journal of the American Academy of Orthopaedic Surgeons, 2000)
Stress fractures are common overuse injuries seen in athletes and military recruits. The pathogenesis is multifactorial and usually involves repetitive submaximal stresses. Intrinsic factors, such as hormonal imbalances, may also contribute to the onset of stress fractures, especially in women. The classic presentation is a patient who experiences the insidious onset of pain after an abrupt increase in the duration or intensity of exercise. The diagnosis is primarily clinical, but imaging modalities such as plain radiography, scintigraphy, computed tomography, and magnetic resonance imaging may provide confirmation. Most stress fractures are uncomplicated and can be managed by rest and restriction from the precipitating activity. A subset of stress fractures can present a high risk for progression to complete fracture, delayed union, or nonunion. Specific sites for this type of stress fracture are the femoral neck (tension side), the patella, the anterior cortex of the tibia, the medial malleolus, the talus, the tarsal navicular, the fifth metatarsal, and the great toe sesamoids. Tensile forces and the relative avascularity at the site of a stress-induced fracture often lead to poor healing. Therefore, high-risk stress fractures require aggressive treatment.